Rare bird documentation form for Bohemian Waxwing at River Heights in north Iowa City, 1978 - Halmi, Nicholas S.et al (1978)
Rare bird documentation form for a Bohemian Waxwing at River Heights in north Iowa City in Johnson County, IA on January 27, 1978. Epson - sheet feed